A Novel QTL for Powdery Mildew Resistance in Nordic Spring Barley (Hordeum vulgare L. ssp. vulgare) Revealed by Genome-Wide Association Study - Bengtsson, Therése; Åhman, Inger; Manninen, Outi; Reitan, Lars; Christerson, Therese; Due Jensen, Jens; Krusell, Lene; Jahoor, Ahmed; Orabi, Jihad (Frontiers in Plant Science, 2017)
The powdery mildew fungus, Blumeria graminis f.sp hordei is a worldwide threat to barley (Hordeum vulgare L. ssp. vulgare) production. One way to control the disease is by the development and deployment of resistant cultivars. A genome-wide association studyIn this study (GWAS) was performed in a Nordic spring barley panel, consisting of 169 genotypes, to identify marker-trait associations significant for powdery mildew. Powdery mildew was scored during three years (2012-2014) in four different locations within the Nordic region. There were strong correlations between data from all locations and years. In total four QTLs were identified, one located on chromosome 4H in the same region as the previously identified mlo locus and three QTLs on chromosome 6H. Out of these three QTLs identified on chromosome 6H, two are in the same region as previously reported QTLs for powdery mildew resistance, whereas one QTL appears to be novel QTL. The top NCBI BLASTn hit of the SNP markers within the novel QTL predicted the responsible gene to be the 26S proteasome regulatory subunit, RPN1, which is required for innate immunity and powdery mildew-induced cell death in Arabidopsis. The results from this study have revealed SNP marker candidates that can be exploited for use in marker-assisted selection and stacking of genes for powdery mildew resistance in barley.